The Application of the Principle of Professionalism by Notaries in the Preparation of Authentic Deeds: Penerapan Asas Profesionalitas Pada Notaris Dalam Pembuatan Akta Autentik - Tahta Fortuna Maharani Wijaya; Ery Agus Priyono (Lex Renaissance, 2024)
This study aims to analyze the application of the principle of professionalism to notaries in making authentic deeds. Authentic deeds are considered as deeds that are perfect evidence in the eyes of the law. In their services to the community, notaries must apply principles, one of which is the principle of professionalism. The principle of professionalism has an urgency to be applied by notaries, especially in making authentic deeds where with the principle of professionalism, the authentic deeds made will achieve the appropriate output. In this regard, this study has a problem formulation, namely "What is meant by the principle of professionalism of notaries?" and "How is the application of the principle of professionalism to notaries in making authentic deeds?" The research method with the type of research is normative research using a statute approach. The object of research refers to the research of legal principles, namely the principle of professionalism. Legal materials consist of primary legal materials, namely laws and regulations and related regulations, and secondary legal materials including journals, theses, and learning modules, so that the method of data collection uses literature study techniques and is then analyzed using qualitative analysis methods. The results of the study indicate that the application of the principle of professionalism in notaries in making deeds can be seen from three applications, namely authentic deed-making services under UUJN and the Code of Ethics and their impacts if violated, legal counseling by notaries related to authentic deeds to support more optimal authentic deed results and the notary's responsibility for the confidentiality of the contents of the deed. The conclusion obtained is that the three applications of the principle of professionalism in notaries in making authentic deeds have a great influence on improving the service and quality of notaries to the community, especially in making authentic deeds.Keywords: Authentic Deed, Professional, Notary AbstrakPenelitian ini bertujuan untuk menganalisis penerapan asas profesionalitas pada notaris dalam pembuatan akta autentik. Akta autentik dianggap sebagai akta yang menjadi alat bukti sempurna di mata hukum. Pada pelayanannya kepada masyarakat, notaris harus menerapkan asas – asas salah satunya asas profesionalitas. Asas profesionalits memiliki urgensi untuk diterapkan notaris khususnya dalam pembuatan akta autentik di mana dengan asas profesionalitas, akta autentik yang dibuat akan mencapai output yang sesuai. Sehubungan dengan hal itu, penelitian ini memiliki rumusan masalah yaitu “Apa yang dimaksud dengan asas profesionalitas notaris?” dan “Bagaimana penerapan asas profesionalitas pada notaris dalam pembuatan akta autentik?”. Adapun jenis penelitiannya adalah penelitian normatif dengan menggunakan pendekatan perundang – undangan (statue approach). Objek penelitian mengacu pada penelitian asas hukum yaitu asas profesionalitas. Bahan hukum terdiri dari bahan hukum primer yaitu peraturan perundang-undangan dan regulasi terkait serta bahan hukum sekunder yang meliputi jurnal, tesis/skripsi, dan modul pembelajaran, sehingga cara pengumpulan data menggunakan teknik studi pustaka kemudian dianalisis dengan metode analisis kualitatif.  Hasil penelitian menunjukkan bahwa penerapan asas profesionalitas pada notaris dalam pembuatan akta dapat dilihat dari tiga penerapan yaitu pelayanan pembuatan akta autentik sesuai dengan UUJN dan Kode Etik dan dampaknya jika melanggar, penyuluhan hukum oleh notaris terkait akta autentik untuk mendukung hasil akta autentik yang lebih maksimal dan tanggung jawab notaris terhadap kerahasiaan isi akta. Kesimpulan yang didapatkan adalah ketiga penerapan asas profesionalitas pada notaris dalam pembuatan akta autentiktersebut sangat berpengaruh terhadap peningkatan pelayanan dan kualitas notaris kepada masyarakat khusunya dalam pembuatan akta autentik.Kata Kunci: Akta Autentik, Profesional, Notaris